Factors Associated With HSV PCR CSF Testing and Empiric Acyclovir Therapy in Young Febrile Infants. (October 2019) - Swartz, Sheila; Hadjiev, Jennifer; Kolinski, Julie; Chou, Erica; Allen, Katherine; Yan, Ke; Havens, Peter L.
Herpes simplex virus (HSV) infection in infants is a devastating disease with an often subtle presentation. We examined cerebrospinal fluid (CSF) HSV PCR (polymerase chain reaction) testing and empiric acyclovir therapy in young febrile infants. Chart review identified hospitalized infants aged ≤60 days with fever ≥38°C who had undergone lumbar puncture. Previously published criteria were used to define patients at high risk for HSV. Primary outcomes were CSF HSV PCR testing and empiric acyclovir therapy. Of 536 febrile infants, 23% had HSV testing; empiric acyclovir was started in 15%. HSV testing and therapy were associated with younger age, seizure, maternal vaginal lesions, postnatal HSV contact, vesicles, poor tone, CSF pleocytosis, and enteroviral testing. Sixty-two percent of high-risk infants did not undergo HSV testing, and 75% did not receive acyclovir. High-risk infants were untested and untreated at relatively high rates. Evidence-based criteria to guide HSV testing and treatment are needed.